(3NOeGJ GdeYdheGJ GdeMhSHI hab fXGe (BWINISISs - (3eDjO jMji(B, (3NVjQs ((3YeGf(B:s (3OLdI(B,s, 2008)
(3JYQja NOeGJ GdeYdheGJ CgejJgG UaGJgG h JcfhdhLjJgG , MhSHI NOeGJ GdeYdheGJ h eQGMd gPg GdMhSHI , CfhGY NOeGJ GdeYdheGJ GdeMhSHI , OhQI MjGI fXGe GdeYdheGJ h GdYfGUQ GdGSGSjI GdJj jJchf efgG GdfXGe , bhGYO GdHjGfGJ h eda GdHjGfGJ eYGdJWQb Gdi NWhGJ HfGA bGYOI GdHjGfGJ dfXGe (BWINISIS .s
Keywords: (3GdMhGSjHs; (3JcfhdhLjG GdeYdheGJs; (3NOeGJ GdeYdheGJs; (3bhGYO GdHjGfGJs